Konsep Otoritarianisme dalam Pemikiran Zainal Arifin Mochtar di Indonesia Perspektif Siyasah Dusturiyyah - Hasnul Fahreza; Khalid (Bahasa Indonesia, 2026)
This study examines the transformation of authoritarianism in post-1998 Reform Indonesia through a critical analysis of the thought of Zainal Arifin Mochtar, employing the perspective of siyasah dusturiyyah (Islamic constitutional law) as a normative framework of analysis. This research is motivated by an academic gap, in that previous studies on Mochtar’s ideas have largely been confined to the perspective of positive constitutional law and political science alone, without integrating them with the principles of Islamic statecraft. This qualitative research, employing a character-study design, uses a library research method with content analysis applied to Mochtar’s principal works, particularly Kronik Otoritarianisme Indonesia. The findings indicate that Mochtar’s concept of authoritarianism is multidimensional and does not represent a linear continuation of previous authoritarian regimes, but rather a new form that adapts within democratic institutions themselves, manifested in three main patterns: electoral authoritarianism, executive-legislative political cartelization, and the progressive shrinking of civil liberties. Evaluated through the principles of syura (consultation), ‘adl (justice), the prohibition of al-istibdad (despotism), muhasabah al-hukkam (oversight and accountability of rulers), and huquq al-insan (human rights) within the framework of maqashid al-syari‘ah, these three patterns are found to contradict the values of Islamic constitutionalism, and are thus interpreted as a renewed form of despotism (al-istibdad al-mutajaddid). This study recommends the reconstruction of a more just Indonesian constitutional system through the strengthening of substantive syura, judicial independence, the expansion of public participation, and the protection of religious minority rights as an embodiment of hifz al-din